1999
DOI: 10.1002/lt.500050507
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of continuing bone recovery at a mean of 7 years after liver transplantation

Abstract: Patients with end-stage liver disease have low bone-turnover osteoporosis, and there is often further bone loss of 20% to 30% after orthotopic liver transplantation (OLT). Bone recovery after OLT has been reported, but data are limited. We undertook studies to determine whether bone recovery continues in the long term. Twenty-eight adult patients alive at least 5 years after OLT were studied (14 men, 14 women). Bone mineral density (BMD), serum parathyroid hormone (PTH), osteocalcin, and vitamin D levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 33 publications
3
38
2
1
Order By: Relevance
“…8 The mechanisms underlying this early increase have not been established but may be related to vitamin D deficiency, intestinal calcium malabsorption,or reduced renal tubular reabsorption of calcium. An increase in plasma parathyroid hormone levels has been more consistently noted after longer-term followup 15,20,22,23,27,33 and may be related to cyclosporin-induced renal dysfunction.…”
Section: Secondary Hyperparathyroidismmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The mechanisms underlying this early increase have not been established but may be related to vitamin D deficiency, intestinal calcium malabsorption,or reduced renal tubular reabsorption of calcium. An increase in plasma parathyroid hormone levels has been more consistently noted after longer-term followup 15,20,22,23,27,33 and may be related to cyclosporin-induced renal dysfunction.…”
Section: Secondary Hyperparathyroidismmentioning
confidence: 99%
“…In a smaller study of 28 patients, spine bone mineral density had returned to pre-transplantation levels by a mean of 85 months. 27 However, Monegal et al 15 reported recovery of bone mineral density in the spine but not the proximal femur by 36 months after transplantation and Hamburg et al 14 found that recovery of bone mineral density was often incomplete up to 15 years post-transplantation.…”
Section: Changes In Bone Mineral Density After Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Interestingly, bone recovery continues for up to 2 to 7 years after transplantation. [52][53][54] Crosbie et al 55 reported that accelerated bone loss in the transplant setting is caused by more bone resorption exceeding bone formation. Furthermore, calculation of an uncoupling index (osteocalcin-deoxypyridinoline) correlated well with bone mineral density and may serve as a noninvasive means to identify high-risk individuals.…”
Section: Bone Diseasementioning
confidence: 99%
“…verificaram recuperação da densidade mineral óssea após 7 anos de acompanhamento, ultrapassando os valores pré-transplante (49). Em um estudo menor, envolvendo 28 pacientes, a DMO retornou aos níveis pré-transplante em 85 meses (50). Entretanto, Hamberg SM e cols.…”
Section: Transplante Hepáticounclassified